(untitled) (Journal of Hama University, 2025)
The study of silent sounds is one of the most important topics addressed in vocal studies, and from here the research attempts to shed light on the throat sounds and their connotations in the Jewish poetry of Samuel Hanagid Ibn al-Nagrilah. The importance of the topic is highlighted in the fact that it examines the vocal level in the poetry of Jews in the Middle Ages, especially the throat sounds. Perhaps its importance comes from it being the first academic research that studies the throat sounds of the poet Samuel Hanagid. The research begins by explaining the components of the phonetic system, then talks about the letters and sounds in the Hebrew language and the origins of the letters. It then moves on to studying the velar sounds in the poet’s poetry according to the statistical ratios and multiple connotations of each sound. The research concluded with a set of findings. We adopted the descriptive analytical approach in studying the examples and evidence that we derived from the poet’s collection, which we adopted as a main source for the research.